Customer behavior and perception of the luxury market in the context of the CEE region - Chlistovská, Johana (2022)
The Master’s thesis is conducted with the aim to analyze specific behavior of customers and branding specifics in the luxury market as well as business drivers in the CEE region, particularly in the Czech luxury market. The goal of the study is to reveal customers’ perceptions and shopping preferences of luxury goods and how they make their purchase decisions. In order to conduct research, primary data was collected. Two research methods were used in to conduct the study, quantitative and qualitative methods. The literature review covers the luxury industry overview and development. The data analysis part is focused on analyzing the expert’s interviews, and in-depth interviews and then quantifying the findings. The results of the study show that the market changed dramatically after the pandemic and that in the majority, local people are purchasing luxury goods in the Czech Republic. Customers seek excellent services, and they mostly prefer offline purchases.